Twisting the TAPPs: bay-substituted non-planar tetraazapero-pyrenes and their reduced anions - Günther, Benjamin; Höfener, Sebastian; Zschieschang, Ute; Wadepohl, Hubert; Klauk, Hagen; Gade, Lutz H. (Chemistry - a European journal, 2019)
A new synthesis of tetraazaperopyrenes (TAPPs) starting from a halogenated perylene derivative 3,4,9,10- tetrabromo-1,6,7,12-tetrachloroperylene (1) gave access to bay-substituted TAPPs for the first time. Selective lithiation of the bromine-positions and subsequent addition of tosyl azide led to the formation of the tetraazidotetrachloroperylene (2), which was subsequently reduced by addition of sodium borohydride to the corresponding tetraaminotetrachloroperylene (3). Oxidation to its semiquinoidal form 4 and subsequent cyclization with acid chlorides gave rise to a series of bay-chlorinated TAPPs. Whereas the aromatic core of the previously studied ortho-substituted TAPPs was found to be planar, the steric pressure of the two chlorine substituents on each side leads to the twist of the peropyrene core of approximately 30 degrees, a structural feature also observed in other bay-substituted perylene derivatives. An experimental and computational analysis reveals that introducing chloride substituents at these positions leads to slightly increased electron affinities (EA) enabling the selective generation and characterization of the reduced mono-anionic radicals and closed shell di-anionic species. These anions were isolated and characterized by UV/Vis spectroscopy and EPR or NMR, respectively. Processing of the bay-chlorinated TAPPs in n-channel organic TFTs revealed electron mobilities of 0.001 to 0.003 cm2 V−1 s−1. These reduced electron mobilities compared to the ortho-halogenated TAPPs are thought to be rooted in the less densely packed solid-state structures.